PLANKTON ABUNDANCE AS BIOINDICATOR OF THE TROPHIC STATUS WATER IN KOMERING RIVER, SERDANG MENANG VILLAGE, PULAU SIRAH PADANG SUB-DISTRICT, OGAN KOMERING ILIR REGENCY - Indah Anggraini Yusanti; Syaeful Anwar; Muhammad Taufan Febrianto (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Komering River is a river that flows in Serdang Menang Village, Sirah Pulau Padang sub district, Ogan Komering Ilir Regency. Most of the community activities around the Komering River are utilizing river water for household activities, agriculture, sand mining and fish farming. With the increasing variety of activities contained in the Komering River, it can have an effect on the quality of the waters. Changes in water quality can be knoen from physical, chemical and biological indicators. For biological indicators, monitoring can be done through the presence of aquatic biota. One of the aquatic biota that is very susceptible to changes in the aquatic environment is plankton. The purpose of this study was to determine the abundance of plankton as a bioindicator of the tropic status of waters in the Komering River.Â  The study was conducted from March to April 2018 at the Komering River in Serdang Menang Village, Sirah Pulau Padang Sub District, Ogan Komering Ilir Regency. The method used is a field survey by determining the sampling station based on purposive random sampling. Sampling was carried out at 3 stations, namely the sand mining area (station 1), the KJA system fis cultivation area (station 2) and the densely populated residential area (station 3). Based on the result of study, the composition of plankton found in the Komering River consisted of phytoplankton (Bacillariophyceae, Chlorophyceae, Cyanophyceae) and zooplankton (Mastigophora, Monogononta, Crustaceans). The highest abundance index of phytoplankton and zooplankton is found in station 2 (dense area of floating net cages) which iis 3.140 individuals/liter and 100 individuals/liter.Â  Trophic status of Komering River waters in Serdang Menang Village based on phytoplankton abudance including oligotrophic waters, while based on zooplankton abudance including mesotrophic waters.